Effect of glucose variability on pathways associated with glucotoxicity in diabetes: Evaluation of a novel in vitro experimental approach - Chalásová, Katarína; Pácal, Lukáš; Šoupal, Jan; Prázný, Martin; Kaňková, Kateřina (Diabetes research and clinical practice, 2016)
AIMS: Glycaemic variability (GV) has been hypothesized to increase the risk of diabetes complications; however, results of clinical studies are contradictory. The effect of GV on cell phenotypes has been investigated in vitro showing that GV may have more deleterious effect on cells that high glucose itself. However, methodology used to study GV in vitro differs significantly between studies and does not reflect in vivo situation. Therefore we aimed to establish clinically relevant an in vitro experimental approach for the study of GV that reflects intra-day glucose fluctuations of subjects with type 1 diabetes mellitus (T1DM) and of healthy subjects and to test how low and high GV affect expression of genes that protects cells from hyperglycaemia-induced damage. METHODS: Human umbilical vein endothelial cells (HUVEC) were cultured 24h in medium with different glucose profiles: high GV, low GV and GV of healthy subjects-profiles created according to CGM of T1DM patients and healthy subjects. These profiles were compared to commonly used 5.5 and 25mmol/l glucose concentrations. Gene expression was determined using quantitative PCR. RESULTS: Our results showed general down-regulation of enzymes that are involved in the protection against hyperglycaemia-induced intracellular changes in both low and high GV compared to normal glycaemia similarly to the decrease induced by continuous hyperglycaemia. Gene expressions did not differ between high and low GV. CONCLUSION: Our data indicate that GV may have similar or even greater effect than continuous hyperglycaemia on the expression of several genes relevant to pathogenesis of diabetes microvascular complications.
Keywords: techniky in vitro; Humans; Case-Control Studies; messenger RNA; Oligonucleotide Array Sequence Analysis; studie případů a kontrol; polymerázová řetězová reakce s reverzní transkripcí; lidé; Biomarkers; kvantitativní polymerázová řetězová reakce; Blood Glucose; proliferace buněk; Cells, Cultured; Reverse Transcriptase Polymerase Chain Reaction; glukosa; hyperglykemie; Human Umbilical Vein Endothelial Cells; apoptóza; hypoglykemie; Hyperglycemia; diabetes mellitus 1. typu; Hypoglycemia; RNA, Messenger; biologické markery; krevní glukóza; kultivované buňky; endoteliální buňky pupečníkové žíly (lidské); Cell Proliferation; stanovení celkové genové exprese; Glucose; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; In Vitro Techniques; Real-Time Polymerase Chain Reaction; Gene Expression Profiling; Apoptosis; Diabetes Mellitus, Type 1